\(2x-\frac{1}{5}=\frac{6}{5}x-\frac{1}{2}\\ \Rightarrow2x-\frac{6}{5}x=\frac{1}{5}-\frac{1}{2}\\ \Rightarrow\frac{4}{5}x=-\frac{3}{10}\\ \Rightarrow x=-\frac{3}{10}:\frac{4}{5}=-\frac{3}{10}.\frac{5}{4}=-\frac{3}{8}\)
vậy ...
\(2x-\frac{1}{5}=\frac{6}{5}x-\frac{1}{2}\)
\(\Rightarrow2x-\frac{6}{5}x=\left(-\frac{1}{2}\right)+\frac{1}{5}\)
\(\Rightarrow\frac{4}{5}x=-\frac{3}{10}\)
\(\Rightarrow x=\left(-\frac{3}{10}\right):\frac{4}{5}\)
\(\Rightarrow x=-\frac{3}{8}\)
Vậy \(x=-\frac{3}{8}.\)
Chúc bạn học tốt!